Analysis of Dependency Ratio and Sex Ratio on Economic Growth and HDI in Aceh Tamiang District - Aulia Afandi; Andika Pratama; Darmawansyah (Formosa Journal of Science and Technology, 2023)
The purpose of this research is to analyze the effect of dependency ratio and sex ratio on economic growth and HDI in Aceh Tamiang district, both partially and simultaneously. The results showed that partially the dependency ratio variable had a positive and significant effect on economic growth and HDI in Aceh Tamiang district. While the sex ratio variable partially has a negative and insignificant effect on economic growth in Aceh Tamiang district. Simultaneously the dependency ratio and sex ratio variables have a significant influence on economic growth in Aceh Tamiang district.The purpose of this research is to analyze the effect of dependency ratio and sex ratio on economic growth and HDI in Aceh Tamiang district, both partially and simultaneously. The results showed that partially the dependency ratio variable had a positive and significant effect on economic growth and HDI in Aceh Tamiang district. While the sex ratio variable partially has a negative and insignificant effect on economic growth in Aceh Tamiang district. Simultaneously the dependency ratio and sex ratio variables have a significant influence on economic growth in Aceh Tamiang district.